Spectrophotometric Determination of Nickel with 3-Hydroxy-3-methyl-1-p-methoxy phenyl Triazene - Bhatt, Rekha; S. Chhangani, Manojkumar; Goswami, A.K.; Dashora, Rekha; Purohit, D.N. (Asian Journal of Chemistry, 2010)
3-Hydroxy-3-methyl-1-p-methoxy phenyl triazene has been established as a new reagent for spectrophotometric determination of nickel.